Specialized Pro-resolving Lipid Mediators and Glial Cells: Emerging Candidates for Brain Homeostasis and Repair - Tiberi, Marta; Chiurchiù, Valerio (Frontiers in Cellular Neuroscience, 2021)
Astrocytes and oligodendrocytes are known to play critical roles in the central nervous system development, homeostasis and response to injury. In addition to their well-defined functions in synaptic signaling, blood-brain barrier control and myelination, it is now becoming clear that both glial cells also actively produce a wide range of immune-regulatory factors and engage in an intricate communication with neurons, microglia or with infiltrated immune cells, thus taking a center stage in both inflammation and resolution processes occurring within the brain. Resolution of inflammation is operated by the superfamily of specialized pro-resolving lipid mediator (SPMs), that include lipoxins, resolvins, protectins and maresins, and that altogether activate a series of cellular and molecular events that lead to spontaneous regression of inflammatory processes and restoration of tissue homeostasis. Here, we review the manifold effects of SPMs on modulation of astrocytes and oligodendrocytes, along with the mechanisms through which they either inhibit inflammatory pathways or induce the activation of protective ones. Furthermore, the possible role of SPM in modulating the cross-talk between microglia, astrocytes and oligodendrocytes is also summarized. This SPM-mediated mechanism uncovers novel pathways of immune regulation in the brain that could be further exploited to control neuroinflammation and neurodegeneration.